Accelerating Effect of DMAP on CuI Catalyzed Buchwald‐Hartwig C‐N Coupling: Mechanistic Insight to the Reaction Pathway. Issue 45 (2nd December 2019) - Roy, Subhasish; Dutta, Mintu Maan; Sarma, Manas Jyoti; Phukan, Prodeep
Abstract: An efficient methodology has been developed for C−N cross‐coupling reaction between aryl halide and amine using a catalytic system comprised of CuI and N, N ‐dimethyl amino pyridine (DMAP). Coupling reactions were carried out in DMSO at 120 °C in presence of 5 mol% CuI, 20 mol% DMAP and 2.5 equivalent of KOH. Addition of DMAP was found to be beneficial in accelerating the rate of reaction significantly. Both aryl iodides and aryl bromides could be successfully coupled with different primary and secondary amines to furnish the desired cross‐coupling product in high yield. A copper complex [Cu(DMAP)4 I]I made by combining CuI and DMAP was found to produce superior result for the Buchwlad‐Hartwig cross coupling reaction. The use of 2 mol% of the copper complex is sufficient to produce high yield of the product. Abstract : An efficient methodology has been developed for Buchwlad‐Hartwig C−N cross‐coupling reaction between aryl halide and amine using a catalytic system comprised of CuI and N, N ‐dimethyl amino pyridine (DMAP). Coupling reactions were carried out in DMSO at 120 °C in presence of 5 mol% CuI, 20 mol% DMAP and 2.5 equivalent of KOH. Addition of DMAP was found to be beneficial in accelerating the rate of reaction significantly. Both aryl iodides and aryl bromides could be successfully coupled with different primary and secondary amines to furnish the desired cross‐coupling product in high yield. A copper complex [Cu(DMAP)4 I]I made by combining CuI and DMAP was found to produce superior result for the C−N cross coupling reaction. The use of 2 mol% of the copper complex is sufficient to produce high yield of the product under the same reaction condition.